Maillard reaction between oligopeptides and reducing sugar at body temperature: The putative anti-glycation agents - Wang, Qiang; Xiang, Xiaofeng; Xie, Yuejie; Wang, Kai; Wang, Cao; Nie, Xuyuan; Wang, Puzhi (Frontiers in Nutrition, 2022)
Type 2 Diabetes mellitus (T2DM) is one of the most common chronic multifactorial diseases, which is associated with the increased concentration of glucose in the blood. Therefore, the utilization of blood lowering agents is clearly a promising approach that can lead to a suppression of the evaluated blood glucose, and thus curing T2DM and other complication. In this study, we evaluated the glucose lowering effect of a varieties of amino acids (alanine and histidine), dipeptides (carnosine and (-alanine-L-histidine), and tripeptide (glutathione) by reacting with glucose, fructose, and sucrose under 37 oC and pH 7.4 to mimic their processing in physiological condition. By measuring the reduction of reactants and the formation of Maillard reaction products over the course of 21 days’ storage, we found that the glucose lowering effect of carnosine was better than the rest of the counterparts. The histidine residue of in carnosine may contribute to its glucose lowing effect while beta-amino acid -alanine residue could facilitate the glucose lowering effect of carnosine by maintaining its chemical stability during the storage. These results may open up new avenues for the applications of bioactive peptide carnosine as a natural blood sugar level lowering agent to control T2DM.